International radical trachelectomy assessment: IRTA study. (March 2019) - Salvo, Gloria; Ramirez, Pedro T; Leitao, Mario; Cibula, David; Fotopoulou, Christina; Kucukmetin, Ali; Rendon, Gabriel; Perrotta, Myriam; Ribeiro, Reitan; Vieira, Marcelo; Baiocchi, Glauco; Falconer, Henrik; et al.
Abstract : Background: Radical trachelectomy is considered a viable option for fertility preservation in patients with low-risk, early-stage cervical cancer. Standard approaches include laparotomy or minimally invasive surgery when performing radical trachelectomy. Primary Objective: To compare disease-free survival between patients with FIGO (2009) stage IA2 or IB1 (⩽2cm) cervical cancer who underwent open versus minimally invasive (laparoscopic or robotic) radical trachelectomy. Study Hypothesis: We hypothesize that minimally invasive radical trachelectomy has similar oncologic outcomes to those of the open approach. Study Design: This is a collaborative, multi-institutional, international, retrospective study. Patients who underwent a radical trachelectomy and lymphadenectomy between January 1, 2005 and December 31, 2017 will be included. Institutional review board approval will be required. Each institution will be provided access to a study-specific REDCap (Research Electronic Data Capture) database maintained by MD Anderson Cancer Center and will be responsible for entering patient data. Inclusion Criteria: Patients with squamous, adenocarcinoma, or adenosquamous cervical cancer FIGO (2009) stages IA2 and IB1 (⩽2 cm) will be included. Surgery performed by the open approach or minimally invasive approach (laparoscopy or robotics). Tumor size ⩽2 cm, by physical examination, ultrasound, MRI, CT, or positron emission tomography (at least one should confirm a tumor size ⩽2 cm). Centers must contribute at least 15 cases of radical trachelectomy (open, minimally invasive, or both). Exclusion Criteria: Prior neoadjuvant chemotherapy or radiotherapy to the pelvis for cervical cancer at any time, prior lymphadenectomy, or pelvic retroperitoneal surgery, pregnant patients, aborted trachelectomy (intra-operative conversion to radical hysterectomy), or vaginal approach. Primary Endpoint: The primary endpoint is disease-free survival measured as the time from surgery until recurrence or death due to disease. To evaluate the primary objective, we will compare disease-free survival among patients with FIGO (2009) stage IA2 or IB1 (⩽2cm) cervical cancer who underwent open versus minimally invasive radical trachelectomy. Sample Size: An estimated 535 patients will be included; 256 open and 279 minimally invasive radical trachelectomy. Previous studies have shown that recurrence rates in the open group range from 3.8% to 7.6%. Assuming that the 4.5-year disease-free survival rate for patients who underwent open surgery is 95.0%, we have 80% power to detect a 0.44 HR using α level 0.10. This corresponds to an 89.0% disease-free survival rate at 4.5 years in the minimally invasive group.